A Survey Study of Japanese Managers' Views of Business Ethics - Nakano, Chiaki (Journal of business ethics, 1997)
In the United States, a series of survey studies have been done to examine corporate managers' views of business ethics and various business practices (Baumhart, 1961; Brenner and Molander, 1977; Vitell and Festervand, 1987). This paper is a replication study conducted in Japan of those American studies. The results of the study suggest that Japanese managers tend to be more situational in their ethical orientation than Americans. The results also show that the company policy on ethics is the most important factor influencing Japanese managers' ethical decisions.